Interactive English Learning with Multimedia at YPK Karya High School - Aprillia, Aprillia; Andayani, Endang Sri; Chodidjah, Chodidjah (INTERACTION: Jurnal Pendidikan Bahasa, 2023)
In the world of education, multimedia is used as an effective, attractive, efficient, and easy-to-use learning media in terms of learning assessment. Currently, the method of learning English at YPK Karya High School is still face-to-face and textbooks, the difficulty of students cannot listen to the speech and vocabulary sentences conveyed by the teacher and cannot write the vocabulary sentences correctly, therefore researchers make alternative English learning with multimedia, as an easy and interactive learning solution. The model used is ADDIE, and there are 5 stages: analysis, design, development, implementation, and evaluation. The subjects in this study were 1 principal, 2 teachers, 3 students. The methods used to collect data were interviews and observations. After obtaining the results of the analysis, the researcher designs the device requirements and multimedia design with the aim of providing a complete picture of the application. The design was performed using the Flash Professional CS5 application, an application specifically designed to create animation, and Photoshop 7.0 for image creation. Finally, the application for failures, system errors, and application maintenance. The results of the research on interactive learning English with multimedia are very helpful for students of SMA YPK Karya Tangerang because it is simpler and easier to repeat.